Integrated MagnetoTelluric and seismic reflection study: Skellefte Ore District, northern Sweden - Juanatey, M.; HÜBert, J.; Juhlin, Christopher; Malehmir, A.; Tryggvason, A. (2011)
The Skellefte District is a very rich mining area in northern Sweden. The main deposits consist of volcanic-hosted massive sulphides VHMS rich in zinc, copper, lead, gold and silver. Since the area has been mined and explored for over a century, today's challenge is to locate deeper deposits. The VINNOVA 4D modeling project aims to address this challenge by understanding the regional setting of the district and its evolution over time. © 2011 Society of Exploration Geophysicists.